Stability indicator for defining environmental and protective requirements for landscape ecosystems - Zhou, Chengjun; Boyko, Taras; Ruda, Mariia; Shybanova, Alla; Dzhumelia, Elvira; Kochan, Orest; Levkiv, Mariana (Journal of Environmental Engineering and Landscape Management, 2024)
Methodological aspects of assessing harmful impacts on the natural environment are presented, aimed at determining the indicator of ecosystem stability. The use of such an indicator makes it possible to determine environmental changes as a result of anthropogenic activity, as well as to determine the significance of these changes. A system is presented that systematizes the variety of consequences of anthropogenic impact on CLS. A qualitative scale of reducing harmful anthropogenic impact is proposed. It is proposed to conduct assessment of the categories of significance of harmful effects and ecological risk on the basis of a comprehensive evaluation of impacts on individual storeys and subsystems in the compartment from different sources of influence, taking into account their magnitude and intensity. The corresponding scales, a way of complex formation, categories of impact significance have been developed; also, an example of constructing an environmental risk matrix has been presented.